PERAN PENTING PERSONAL SELLING DALAM KEPUTUSAN PEMBELIAN KOSMETIK LT PRO DI LUWES GENTAN SUKOHARJO - Yusuf Eko Saputro; Burhanudin Burhanudin; Ratna Damayanti (JURNAL ILMIAH EDUNOMIKA, 2020)
This study aims to determine the effect simultaneously and partially Personal Selling (X1), Promotion (X2), and Product Quality (X3) on Purchasing Decisions (Y). The population in this study are all LT Pro consumers in Luwes Gentan Sukoharjo. Researchers used a purposive sampling technique in taking samples, so the number taken was 100 respondents. Data collection techniques with questionnaires. The analysis used is Multiple Liner Regression Analysis. The results of Personal Selling, Promotion, and Product Quality Simultaneously influence the Purchasing Decision. And basedaon theat test of Personal Selling partially does not affect the Purchasing Decision, Promotion partially influences the Purchasing Decision, Product Quality partially influences the Purchasing Decision. Keywords : Personal Selling, Promotion, Product Quality, Purchasing Decisions